How Ethical Leadership Is Practiced in Public Bureaucracy: A Qualitative Inquiry - Jemi Pabisangan Tahirs; Otto Randa Payangan; Angelino Dos Santos; Muhammad Ichwan Musa; Yogi Hady Afrizal (Ilomata International Journal of Management, 2026)
This study explores how ethical leadership is practiced and experienced by senior bureaucratic leaders in Indonesian public institutions. Using a qualitative phenomenological approach, data were collected through in-depth interviews and document analysis involving eight experienced leaders from central and regional government organizations. The findings reveal three interrelated dimensions of ethical leadership: exemplary behavior, moral courage in high-risk decision-making, and relational justice toward subordinates, particularly in regulatory gray areas. These results suggest that ethical leadership is enacted as a contextually grounded and reflective moral practice, extending beyond formal compliance. The study highlights the relevance of integrating moral reasoning into leadership development while providing an experience-based perspective on ethical leadership in public administration.